Contact dermatitis due to local cosmetics: A study from Northern India - Sheena Goyal; Naheed Sajid; Sajid Husain (Wolters Kluwer Medknow Publications, 2019)
Background: Majority of the cosmetics are synthetic in nature and capable of causing dermatitis among frequent users. Some cosmetics (bindi, sindoor, etc.) that cause serious skin inflammation are specific to Indian culture. Aim: To study the prevalence of contact dermatitis due to various cosmetics indigenous among Indian users. Materials and Methods: A cross-sectional study of 2,150 patients who attended dermatitis clinic at a regional hospital in north India. A total of 400 of these were suspected of cosmetic dermatitis based on clinical grounds and were subjected to patch test using Indian Standard Series and Cosmetic series kit. Results: Among the 400 patients identified for cosmetic dermatitis, 352 (88%) were female and 326 (81.5%) between 20 and 49 years of age. Bindi/kumkum (30%), hair dye (18%), and deodorant/perfume (14%) were primary cosmetics causing contact dermatitis. Patch test with the suspected cosmetics was positive in 52.75% cases. Patients who visited their doctor in the early stages of appearance of symptoms (<3 months) were more likely to have positive patch test. Conclusion: Higher incidence of cosmetic dermatitis is observed in adult females aggravated by use of inferior quality cosmetics. Early detection of the disease can be helpful.